Improving Disaster Mitigation Understanding Through Disaster Map-Based Worksheets Learning in Social Science Subjects - Prasetya, Sukma Perdana; Sitohang, Lidya Lestari; Rindawati; Ibrahim, Mohd Hairy (Journal of disaster research, 2025)
This study examines the effects of disaster-map-based worksheets on improving students’ understanding of disaster mitigation. Research was conducted on class VII students at SMP Plus Al-Fatimah in Bojonegoro District, which is prone to floods and landslides. The following study used pretest-posttest for 62 students as subjects. The study subjected students to four meetings of learning using disaster-map-based worksheets to visualize areas susceptible to disasters in the region. The data showed a significant change in the students’ understanding, mainly in aspects of interpretation, perspective, empathy, and reflection with respect to mitigation concept understanding. Disaster map-centered education truly works as a well-fitted way for students to understand and practice relevant, more realistic scenery of disaster mitigation steps. The design of the worksheet can still be enhanced to be more attractive and easy to comprehend by students. The use of some technology such as Canva and Google Sites would be effective in establishing high interactivity and flexibility for learning. This then concludes that the worksheet using disaster map approach could be implemented in other disaster hazard areas to increase awareness of and preparedness for disasters among the youth.